Chalcogen controlled redox behaviour in peri-substituted S, Se and Te naphthalene derivatives. (11th November 2022) - Roemmele, Tracey L.; Knight, Fergus R.; Crawford, Ellis; Robertson, Stuart D.; Bode, Bela E.; Bühl, Michael; Slawin, Alexandra M. Z.; Woollins, J. Derek; Boeré, René T.
Abstract : Chemically reversible electron transfers between neutral, cation radical and dication naphthalenic peri -1, 8-diphenylchalcogenides are governed by chalcogen (SS, SSe, STe, SeSe, SeTe, TeTe) contributions to the redox molecular orbitals. Abstract : Cyclic and square wave voltammetry of (PhE)2 peri -disubstituted naphthalene[1, 8- cd ]dichalcoganyls and acenaphthene[5, 6-diyl]dichalcoganyls (E = S, Se, Te, 12 compounds) is reported. Mixed (E1 = Se, Te; E2 = Br, I) naphthalene[1, 8- cd ]halochalcoganyls were also investigated, as well as an exemplar bearing two PhS(O) groups and another bearing one PhSe and one Ph2 P(S) substituent. The voltammetry, in CH2 Cl2 /0.4 M [ n Bu4 N][PF6 ] at both platinum and glassy carbon macro-disk working electrodes, shows two sequential chemically reversible and electrochemically quasi-reversible oxidation processes, and the lack of accessible reductions. Additional oxidations above +1.5 V vs. Fc +/0 have not been investigated in detail. In situ and ex situ EPR spectroscopy conclusively demonstrate that both anodic processes are 1e transfers; persistent radical cations could be generated for all the dichalcoganyls except when E1 = E2 = Te; for the latter case thermally stable dications are generated instead. The complex possible solution conformations of these compounds in 0, +1 and +2 charge states were modelled with DFT at the B3LYP-D3(BJ)/6-31+G(d) level of theory in a CH2 Cl2 PCM continuum solution model and adiabatic ionisation energies calculated, which correlate linearly ( R = 0.88) with the E a1p values. Crystal structures of four solvolysis and hydrolysis products of the ditellurium dications are reported and were modelled computationally. Interpretative comparisons to unsubstituted naphthalene[1, 8- cd ]dichalcogenoles are reported and the crystal structure of naphtho(1, 8- cd )(1, 2-dithiolium) tetrafluoroborate has been obtained. This is the first structure reported for any salt of this cation radical. Electron transfer mechanisms of both the (PhE)2 and E2 peri -disubstituted naphthalene series are correlated using a redox molecular orbital interpretative framework.